A study on maternal-fetal attachment in pregnant women undergoing fetal echocardiography - Concetta Polizzi; Giovanna Perricone; Vincenzo Duca; Antonio Carollo; Mariangela Marceca; Valentina Fontana (Hygeia Press di Corridori Marinella, 2017)
Purpose: To investigate the possible effects of the fetal echocardiography experience on the prenatal attachment process. The predictive effect of specific women's psychological variables will be explored as well. Design and methods: This between groups study involved 85 women with pregnancy at risk who underwent the fetal echocardiography, and 83 women who were about to undergo the morphological scan. The tools employed were: the Prenatal Attachment Inventory (P.A.I.) to explore the maternal-fetal attachment; the Maternity Social Support Scale to investigate the woman perception of being socially supported during pregnancy; both the Big Five Questionnaire and the FACES III to explore the personality traits of pregnant women and their perception of their couple relationship functioning. Findings: The outcomes of ANOVA do not show statistically significant differences between the two groups of the mothers-to-be with regard to the scores of the P.A.I. (F = .017; p = .897; η2 = .000), while the regression analysis of the possible effect of the maternal psychological variables on the mother-fetus relationship shows a statistically significant result only with regard to the "social support" variable (r2 = .061; df = 80; p = .025). Conclusions: It would seem that the process of the prenatal attachment develops independently whether the woman has to undergo a first level screening or a second level examination such as the fetal echocardiography.